2013
DOI: 10.1108/s0885-3339(2013)0000014005
|View full text |Cite
|
Sign up to set email alerts
|

The Relative Survival of Worker Cooperatives and Barriers to Their Creation

Abstract: This paper argues the conjecture that worker cooperatives (WCs) are rare because of competitive disadvantages relative to conventionally-owned firms (CFs) is not supported by existing research. It surveys research on the survival and failure of WCs and CFs and estimates the nonparametric hazard and survival functions for CFs in the US. Because the rarity of WCs cannot be attributed to performance it must result from a low formation rate. This is traced to wealth and credit constraints, entrepreneurial rents, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 22 publications
0
27
0
Order By: Relevance
“…In Europe, they outperformed their counterparts during and after the financial crisis (Birchall & Ketilson 2009). Similarly, recent studies find that US and Canadian cooperatives have longer survival rates and are more resilient than comparable small for-profit businesses (Olsen 2013, Abell 2014. Thus, cooperative growth appears to depend less on survival rates and more on barriers to entry-that is, whether the institutional conditions exist to support their adoption-particularly financing in the early years.…”
Section: Management and Corporate Governancementioning
confidence: 93%
See 1 more Smart Citation
“…In Europe, they outperformed their counterparts during and after the financial crisis (Birchall & Ketilson 2009). Similarly, recent studies find that US and Canadian cooperatives have longer survival rates and are more resilient than comparable small for-profit businesses (Olsen 2013, Abell 2014. Thus, cooperative growth appears to depend less on survival rates and more on barriers to entry-that is, whether the institutional conditions exist to support their adoption-particularly financing in the early years.…”
Section: Management and Corporate Governancementioning
confidence: 93%
“…The democratic governance model is more difficult to achieve and maintain over time compared to more hierarchical models. The model also sets limits to growth as members cannot sell shares to finance new ventures, they rely on loan finance, and they lack access to external finance (Olsen 2013, Diamantopoulos & Bourgeois 2014.…”
Section: Management and Corporate Governancementioning
confidence: 99%
“…(Dastur 2012, p. 8). It has been recently shown that research in various countries about worker coops shows that the failure rate in the short-and medium-term of worker cooperatives is lower than conventional businesses (Olsen 2013). The worker cooperatives shown to be efficient run private firms with their own managerial hierarchy (Fields 2011, p. 83).…”
Section: Cooperativesmentioning
confidence: 99%
“…Having a say in decision making enables workers to improve their working conditions. It can also foster worker loyalty and a willingness to make sacrifices to help the company weather storms better than similarly positioned conventional firms (see Olsen, ). For example, worker‐owners of Union Cab in Madison chose to give themselves a series of pay cuts to help the company cope with competition from TNCs, which had driven revenue down by 20% (Union Cab board member, interview with author, March 2017).…”
Section: The Taxi Co‐op Alternativementioning
confidence: 99%